2019
DOI: 10.1016/j.adolescence.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

#(Me)too much? The role of sexualizing online media in adolescents’ resistance towards the metoo‐movement and acceptance of rape myths

Abstract: UvA-DARE (Digital Academic Repository) #(Me)too much? The role of sexualizing online media in adolescents' resistance towards the metoo-movement and acceptance of rape myths

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
(92 reference statements)
1
11
1
1
Order By: Relevance
“…Notions of women as sex objects in the study of Maes et al [34] had higher mean scores representing higher notions of women as sex objects (M = 2.64, SD = .71). The sexual health-related subject in Ruppel et al [35] study included medical information seeking covered general information about the conception and pregnancy process, fertility and conception products, services, and medications, concerns about miscarriage.…”
Section: Bystander Prevention Type: Proactive and Reactive In Conjunction With The Bystander Prevention Opportunities Provided Bymentioning
confidence: 71%
See 1 more Smart Citation
“…Notions of women as sex objects in the study of Maes et al [34] had higher mean scores representing higher notions of women as sex objects (M = 2.64, SD = .71). The sexual health-related subject in Ruppel et al [35] study included medical information seeking covered general information about the conception and pregnancy process, fertility and conception products, services, and medications, concerns about miscarriage.…”
Section: Bystander Prevention Type: Proactive and Reactive In Conjunction With The Bystander Prevention Opportunities Provided Bymentioning
confidence: 71%
“…A total of 84 teenagers participated in it, and the participants had access to the PESEDIA, and they share their experiences and feelings about summer school. Respondents in Maes et al [34] study indicated how much time they spend on Facebook, Instagram, Snapchat, WhatsApp, and websites with video clips such as YouTube. Higher scores re ected higher SM use (M = 3.30, SD = 1.40).…”
Section: Use Of Social Mediamentioning
confidence: 99%
“…Sobre los resultados de la validación por estudiantes, se destaca la valoración positiva que realizaron respecto al instrumento al referir que les sensibilizó en relación con las implicaciones del género sobre los problemas y situaciones que enfrentan los/as usuarios/as. Que el estudiantado participante haya reconocido este aspecto resulta de relevancia ya que la literatura es coincidente sobre que, en Chile y en general en los países occidentales, siguen operando patrones culturales entre los jóvenes que reproducen estereotipos y representaciones tradicionales de género que perpetúan la discriminación y la inequidad entre los sexos (Cubillas et al 2016;García y Castro 2017;Maes et al 2019). Dicho en otras palabras, el/la estudiante requiere de un apoyo en su formación para que sea capaz de identificar los sesgos que podrían tener sus propias orientaciones y prejuicios de género sobre el trabajo diagnóstico.…”
Section: Recomendaciones Decisiones Tomadasunclassified
“…This kind of statements can be related to the acceptance of rape myths, which are de ined as "prejudicial, stereotyped or false beliefs about rape, rape victims, and rapists" and communication media may be contributing to these myths. The role of media therefore becomes very important regarding the development of sexist beliefs in adolescents, more precisely, beliefs about different measures to combat sexism such as the #MeToo movement, a movement which may be criticised due to sexual objecti ication, which is fed by sexually explicit material online [21].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, people who use these contents more frequently have greater probability of having attitudes which lead to sexual assault, and participating in acts of this kind, than those who do not use this content, or who do so to a lesser extent [22]. In addition, some men who use pornography show signi icantly higher adverse sexual beliefs, accept the rape myth and sexual conservatism, in greater measure than women who also consume pornography [10,21]. Thus increased research demonstrates that exposure to sexually explicit and violent media may be risk factors regarding partner violence and sexual violence [24].…”
Section: Introductionmentioning
confidence: 99%